Paraesophageal recurrence of hiatal hernia. Radiological diagnosis and laparoscopic surgical resolution - Varela, Martín; Muniz, Nicolás; Pouy, Andrés; Haro, Camila; Mansilla, Sofía (Cirugía del Uruguay, 2022)
The radiological recurrence rate after surgery for type IV large hiatal hernias is close to 50%. Most of the time, recurrence involves a partial ascent of the fundoplication to the thorax (telescoping), and if it does not have clinical expression, conservative management can be chosen (only 3-6% require revision surgery). However, sometimes there are other types of recurrences (paraesophageal) that must be evaluated by functional, endoscopic and radiological studies, which cause dysphagia more frequently. A contrasted upper digestive transit allows in this case to identify the type of hernia recurrence, with partial migration of the gastric fundus towards the left paraesophageal thorax, and a continent fundoplication but technically performed below what is desirable (upper body) (figure). The resolution of the picture implies the reduction of the hernia to the abdominal cavity, with closure of the diaphragmatic defect, dismantling the anterior fundoplication by anatomizing the area and reconfection of a new fundoplication.